Veto Threat Bargaining with a Bicameral Congress. (September 2021) - Guenther, Scott M.; Kernell, Samuel
According to the conventional view, presidents are largely bereft of influence with an opposition-controlled Congress. Congress sends them legislation with a "take it or leave it" choice that maximizes the preferences of the opposition majority while minimizing presidents' preferences. To extricate themselves from this bind, presidents threaten vetoes. Past research suggests that their efforts largely fail, however, for two model-driven reasons: first, veto threats amount to minimally informative "cheap talk, " and second, Congress is a unitary actor with firm control over its agenda. We relax both assumptions, bringing veto rhetoric into a setting more closely resembling real-world conditions. Presidents transmit credible veto threats to a heterogeneous, bicameral Congress where chamber rules enable the minority party to wield some influence over legislation. Examining the legislative histories of all veto-threatened bills passed between 1985 and 2016, we confirm that veto threats ward off about half of veto-targeted legislative provisions—a far greater share than for comparable unthreatened provisions. The House of Representatives is more likely to introduce and pass legislation objectionable to presidents and the Senate is more likely to accommodate presidents, findings consistent with the textbook description of the modern bicameral Congress.